Improving Mental Models and Mental Modelling Ability in Electrical Circuit Context: A Problem-Solving Approach with House Installation Model - Amiruddin Kade; Supriyatman; Marungkil Pasaribu; Ketut Alit adi Untara; Supriyadi (Postgraduate, University of Mataram, 2023)
The purpose of this study was to improve students' Mental Models and Mental Modelling Ability in the context of electrical circuits by using the House Installation Model as a laboratory learning instrument. The problem-solving-based laboratory learning model was applied in this research. The research method utilized a descriptive qualitative research design with a pretest-posttest design. The research results showed that 75% of students experienced Mental Models improvement in the context of electrical circuits, with 15% reaching level 2 and 60% reaching level 3. The improvement in Mental Modelling Ability was also significant, with 80% of students experiencing improvement, 21.7% reaching a moderate level, and 58.7% reaching a high level of Mental Modelling Ability. These results suggest that problem-solving-based practice learning models can effectively improve students' Â Mental Models and Mental Modelling Ability in the context of electrical circuits.